Traditional Environmental Knowledge in a Changing Environment: Vuntut Gwitchin Observations of Change in the Yukon Territory - Consiglio, Erin (Anthropologica)

(untitled) (University of Victoria, 2024)
Scientists, resource managers and developers increasingly seek out Traditional or Indigenous Knowledge to deepen their understanding of the environment. Yet, even as the value of this knowledge is recognized, misperceptions remain; Traditional Knowledge is still often seen as something static, unchanged from one generation to the next rather than as something flexible and adaptive. Ethnographic research with the Vuntut Gwitchin First Nation challenges these perceptions. Their observations of contemporary environmental change in the western Canadian Arctic are becoming part of their Traditional Knowledge, proving that this system of knowledge is resilient and will continue even as the environment becomes ever more unpredictable.